Аналіз міжнародного досвіду розбудови еногастраномічного туризму (освітній та організаційний аспекти) у контексті розвитку виноградарських та виноробних територій України - Петліна, Дарина Вадимівна (Київський національний університет імені Тараса Шевченка, 2016)
Мета. Аналіз міжнародного досвіду розбудови еногастраномічного туризму в освітньому та організаційному аспектах в контексті розвитку виноградарських та виноробних територій України. Методика. На засадах загальнонаукових аналітичних (контент аналізу) та логічних (порівняльних) методів досліджено інформаційні масиви даних офіційних сайтів професійних недержавних громадських інституції у сфері виноробства, виноградарства та еногастрономічного туризму на національному та міжнародному рівні. На засадах методів соціологічного дослідження (інтерв’ю українських експертів у галузі виноградарства, виноробства, туризму та академічної сфери) визначено особливості та проблематику процесу зближення галузей виноградарства та виноробства з туристичною галуззю та його вплав на територію. Результати. Описано міжнародний досвід розбудови еногастраномічного туризму в освітньому та організаційному аспектах в контексті розвитку виноградарських та виноробних територій України. Наукова новизна. Визначено специфіку процесу зближення галузей виноградарства та виноробства з туристичною галуззю в контексті розвитку еногастрономичного туризму в Україні. Даний процес розглядається як один з індикаторів сталого розвитку регіону. Практична значимість. Розроблено практичні рекомендації щодо імплементації в Україні міжнародного досвіду розвитку еногастрономічного туризму.

Aim. Analysis of international experience in enogastronomic tourism development (educational and organizational aspects) in the context of development of winegrowing and winemaking territories in Ukraine. Methodology. Based on the general scientific analytical methods (content analysis) and logical (comparative) methods studied information data from the official websites of professional non-government organizations (NGOs) in the field of viticulture, winemaking and enogastronomic tourism at national and international levels. Based on the sociological research methods (interview with Ukrainian experts in the field of viticulture, winemaking, tourism and academia) determined the main features and challanges in the process of convergence of winegrowing and winemaking industry and tourism, as well as its impact on the territory. Results. Described educational and organizational aspects of international experience in building enogastronomic tourism in the context of development of winegrowing and winemaking territories in Ukraine. Scientific novelty. Established the characteristics of the process of convergence of winegrowing and winemaking industry and tourism industry in the context of enogastronomic tourism development in Ukraine. This process is considered as one of the indicators of sustainable development. The practical significance. Offered practical recommendations for implementation of international experience in enogastronomic tourism in Ukraine.
Analysis of International Experience in Building Enogastronomic Tourism (Educational and Organizational Aspects) in the Context of Development of Winegrowing and Winemaking Territories in Ukraine
Keywords: територія; виноградарство; виноробство; еногастрономія; еногастрономічний туризм; винно-гастрономічний туризм; сталий розвиток; мережа; territory; viticulture; winemaking; enogastronomy; enogastronomic tourism; wine and gastronomic tourism; sustainable development; network